Quantum Annealing with Anneal Path Control: Application to 2-SAT Problems with Known Energy Landscapes (Communications in Computational Physics, 2019)
We study the effect of the anneal path control per qubit, a new user controlfeature offered on the D-Wave 2000Q quantum annealer, on the performance of quantum annealing for solving optimization problems by numerically solving the time-dependent Schrödinger equation for the time-dependent Hamiltonian modeling theannealing problems. The anneal path control is thereby modeled as a modified linearannealing scheme, resulting in an advanced and retarded scheme. The considered optimization problems are 2-SAT problems with 12 Boolean variables, a known uniqueground state and a highly degenerate first excited state. We show that adjustment ofthe anneal path control can result in a widening of the minimal spectral gap by one ortwo orders of magnitude and an enhancement of the success probability of finding thesolution of the optimization problem. We scrutinize various iterative methods basedon the spin floppiness, the average spin value, and on the average energy and describetheir performance in boosting the quantum annealing process.